Functional asymmetry and interhemispheric cooperation in the perception of emotions from facial expressions - Tamietto, Marco; Latini Corazzini, Luca; de Gelder, Beatrice; Geminiani, Giuliano (Experimental brain research, 2006)
The present study used the redundant target paradigm on healthy subjects to investigate functional hemispheric asymmetries and interhemispheric cooperation in the perception of emotions from faces. In Experiment 1 participants responded to checkerboards presented either unilaterally to the left (LVF) or right visual half field (RVF), or simultaneously to both hemifields (BVF), while performing a pointing task for the control of eye movements. As previously reported (Miniussi et al. in J Cogn Neurosci 10:216-230, 1998), redundant stimulation led to shorter latencies for stimulus detection (bilateral gain or redundant target effect, RTE) that exceeded the limit for a probabilistic interpretation, thereby validating the pointing procedure and supporting interhemispheric cooperation. In Experiment 2 the same pointing procedure was used in a go/no-go task requiring subjects to respond when seeing a target emotional expression (happy or fearful, counterbalanced between blocks). Faster reaction times to unilateral LVF than RVF emotions, regardless of valence, indicate that the perception of positive and negative emotional faces is lateralized toward the right hemisphere. Simultaneous presentation of two congruent emotional faces, either happy or fearful, produced an RTE that cannot be explained by probability summation and suggests interhemispheric cooperation and neural summation. No such effect was present with BVF incongruent facial expressions. In Experiment 3 we studied whether the RTE for emotional faces depends on the physical identity between BVF stimuli, and we set a second BVF congruent condition in which there was only emotional but not physical or gender identity between stimuli (i.e. two different faces expressing the same emotion). The RTE and interhemispheric cooperation were present also in this second BVF congruent condition. This shows that emotional congruency is the sufficient condition for the RTE to take place in the intact brain and that the cerebral hemispheres can interact in spite of physical differences between stimuli.